Overview of old-growth forests in Canada from a science perspective - Mosseler, A; Thompson, I; Pendrel, B A (Environmental reviews, 2003)
In response to a broad public concern about the rapidly diminishing area of old-growth forests and their intrinsic biological value, the Canadian Forest Service organized a national symposium in 2001 to discuss the old-growth issue from a science perspective. The objectives were: (i) to bring together Canadian expertise on old-growth forests, (ii) to define old growth within the main forest regions of Canada, (iii) to understand its biological complexities and ecological roles, and (iv) to discuss management and restoration experiences and options. Some forest regions of Canada still contain significant old-growth forest (e.g., some boreal forest regions), although other regions contain very little primary, relatively undisturbed, older forest (e.g., eastern temperate-zone forest regions). One of the difficulties in managing and conserving old-growth forests is defining them in a scientifically meaningful, yet operational and policy-relevant manner. This difficulty may be overcome by developing an index of “old-growthness” (Spies and Franklin 1988) related to specific forest regions or forest types. Such an old-growth index would allow for the inclusion of specific attributes, composition, functions, and processes seen as relevant to different ecological regions or specific forest types and could serve as a basis for prioritizing local or regional conservation and management activities. Thus, such an index approach has worldwide applicability. Traditionally, old-growth forests have been valued primarily as habitat for forest-dependent, specifically old-growth-dependent, wildlife. Recent results from research on old-growth forests in eastern Canada suggest that as tree populations age they tend to increase in genetic diversity and reproductive fitness, suggesting that old-growth forests may serve as natural reservoirs of genetic diversity and reproductive fitness for the constituent tree species. This has important implications for the dispersal and adaptation of trees across increasingly fragmented forest landscapes subject to the anticipated rapid climatic changes and the introduction of new pest and disease problems. Old-growth conservation goes well beyond the more traditional areas of watershed (including water quality) and habitat protection and includes emerging issues such as the conservation of genetic resources and carbon sequestration. It is very much a cross-sectoral issue with many interdisciplinary linkages. Therefore, conservation and protection of old-growth forests should be of wide general interest to the forest sector.